THE SOCIAL IMPACT OF THE COVID-19 PANDEMIC ON PHYSICAL AND MENTAL HEALTH IN INDONESIAN SOCIETY - Yunus, Nur Rohim; Rezki, Annissa (MIZAN: JOURNAL OF ISLAMIC LAW, 2022)
Almost every nation has been affected by the Covid-19 pandemic. The number of people infected with COVID-19 is increasing every day, causing concern in numerous social circles. Starting with the implementation of the lockdown, the PSBB continued and virtually all activities were prohibited by governments in virtually every country on earth, it was alleged, and the number of people exposed to COVID-19 increased. Despite the fact that previously there was a great deal of news based on the assumptions of the community, whether it was generated by rogue elements who exploited the Covid-19 situation for financial gain or because there were people who directly experienced the effects of Covid-19, this is no longer the case. The effects of Covid-19 can no longer be overlooked; not only do physical health problems represent a threat to life but so does mental health, which has far-reaching consequences for society as a whole. Before Covid-19, greeting or introducing oneself by shaking hands was a cultural norm in Indonesia, but it has become an issue for many people. In this study, the author uses a qualitative approach, which simplifies his work, to demonstrate how covid-19 has affected (physical and mental) health and socialization in society.